Altruistic and selfish motivations of charitable giving: Case of the hometown tax donation system in Japan - Eiji Yamamura; Yoshiro Tsutsui; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2017)
In Japan's hometown tax donation system, people can donate to municipalities where they are not resident and in return receive reciprocal gifts from the local governments of those municipalities. A large part of the donated amount can be deducted from their income and residence taxes. This study examined altruistic and selfish motivations in donating money to municipalities where people are not resident through that donation system; we did so using panel data of local governments for 2008-2015. We made the following key findings. (1) The Great East Japan earthquake increased the amount of money donated through that system for local governments with disaster victims. We considered that motivation altruistic. (2) A 1% increase in expenditure for gifts to donors led to a 0.61% increase in donations. We considered that motivation selfish. (3) Compared with donors not receiving gifts, providing gifts to donors led to a reduction in altruistic donations by almost 300%.
Keywords: D64; H23; H84; Z13; 330; Altruism; Charitable giving; Hometown tax donation; Warm glow; Self-interest; Redistribution